Crop Water Productivity and Crop Coefficients of Lentil (Lens Culinaris M.) Under Different Irrigation Regimes (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted for two consecutive winter seasons (2014/15 and 2015/16) at Hudeiba Research Station Farm to determine the effects of deficit irrigation imposed at different developmental stages and throughout the growing season on water use and water productivity of lentil (L. culinaris M.) and to derive the crop coefficient. Lentil Aribo cultivar wasgrown under six irrigation treatments in which one-irrigation was skipped at some of the growth stages, i.e. vegetative (W3), flowering (W4), pod setting (W5) and ripening stage (W6) and irrigation without skipping with intervalsof 10 days (full irrigation) (W1) and irrigation every 15 days (W2) (moderate water stress throughout the growing season). The experimental and/or high cost of irrigation water conditions, if only one irrigation is to be saved, the vegetative and ripening stages could be a safe option.  design was randomized complete block design with three replications. Theaverage estimated values of crop coefficients during the initial, mid -season and late -season stages were 0.28, 1.06 and 0.48, respectively. The results revealed that the highest grain yield was recorded in full irrigation (1003 kgha-1) and significantly (p < 0.001) decreased by 13, 28 and 31% when deficit irrigation was applied throughout the growing season, at flowering and at pod setting stages, respectively. The highest and lowest values of crop waterproductivity resulted from deficit irrigation imposed at vegetative stage and at flowering stages, respectively. The most sensitive stages of lentil to water deficit were the flowering and pod setting. Therefore, under water shortage
Keywords: Lens culinaris M; deficit irrigation; growth stages; grain yield; Water Productivity